If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x)(3x + -2)(x) = 540 Remove parenthesis around (3x) 3x(3x + -2)(x) = 540 Reorder the terms: 3x(-2 + 3x)(x) = 540 Reorder the terms for easier multiplication: 3x * x(-2 + 3x) = 540 Multiply x * x 3x2(-2 + 3x) = 540 (-2 * 3x2 + 3x * 3x2) = 540 (-6x2 + 9x3) = 540 Solving -6x2 + 9x3 = 540 Solving for variable 'x'. Reorder the terms: -540 + -6x2 + 9x3 = 540 + -540 Combine like terms: 540 + -540 = 0 -540 + -6x2 + 9x3 = 0 Factor out the Greatest Common Factor (GCF), '3'. 3(-180 + -2x2 + 3x3) = 0 Ignore the factor 3.Subproblem 1
Set the factor '(-180 + -2x2 + 3x3)' equal to zero and attempt to solve: Simplifying -180 + -2x2 + 3x3 = 0 Solving -180 + -2x2 + 3x3 = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 0=0.3x^2+2x-50 | | x-55=10 | | 2q^3-5q^2-500=0 | | 42-n*n=n | | 1996+43x=0 | | log(10)x+log(10)x-1=log(10)30 | | -24+11=5x+3-4x | | .10(c+3)=-12 | | log(x)+log(x-1)=log(30) | | 21-x=28 | | n-n*n=72 | | 4(a+9)=7[a-(3-a)] | | 9x^2=50x-25 | | 4x-7=36 | | x^3-5x^2+4x-2=0 | | 42x=35x+70 | | 6(4n-4)=-60 | | 8-2n=40 | | 7x+7=-5x+43 | | 49s^2-14s+1=0 | | 8k^2-20=-9k | | 5(7+2)=x-11 | | x-0.4=4.2 | | f(x)=ln(6x) | | 4x+5y+4=0 | | Cos(5x)-cos(3x)=0 | | .2x+13+x=-.10(x+40)+4 | | 10-3(3-2)=8 | | 42r^2=56-r | | (p+6)(p-2)=-7 | | x-1.2-2=-5 | | 144=[2x] |